Agroeduwisata Peluang Dan Tantangan Pengembangan Agroeduwisata Di Desa Waimital Kecamatan Kairatu Kabupaten Seram Bagian Barat - Nasrudin, Muhammad (Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Mataram, 2025)
Agro-edutourism is a form of ecotourism that offers an interesting opportunity to develop regional tourism. By utilizing the potential of nature and biodiversity and combining it with the agricultural sector, agro-edutourism can provide an interesting and educational experience for tourist. This study aims to analyze the opportunities and challenges in the development of agro-edutourism in Waimital Village, Kairatu District, West Seram Regency. A descriptive approach is used to collect data in the form of words. The data collected after being analyzed is then described so that it is easily understood by others. The method used is AHP (Analitical Hierarchy Process). The AHP method is a decision support model this decision support will describe complex multi-factor or multi-criteria problem into a hierarchy. The result of the study showed that Opportunity as the best Alternative with the highest priority score of 0,003417, the second priority is the Actor Party with a score of 0,002907, the third priority is Challenges with a score of 0,002181, and the last is Improvement with a score of 0,001133. Waimital Village has a very high opportunity for agro-edu-tourism development, due to the existence of agriculture, plantation, fisheries, livestock and many other agricultural and livestockindustrial productions that can support the development of agro-edu-tourism in Waimital Village in the future